REVIEWING PROTAGONIST’S CHARACTER DEVELOPMENT BASED ON THE NARRATIVE STRUCTURE IN A MOVIE: A CASE STUDY OF CARRY-ON (2024): AN ANALYSIS BASED ON SYD FIELD’S THREE-ACT STRUCTURE AND LAJOS EGRI’S CHARACTER DIMENSIONS - Nurjanah; Todo Sibuea (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2025)
This study explores how the film Carry-On (2024) is structured narratively and how its protagonist develops throughout the story using Syd Field’s Three-Act Structure and Lajos Egri’s Character Dimensions. As a thriller that follows Ethan Kopek, a young TSA officer dragged into a dangerous situation, the film presents a clear progression of conflict that makes it suitable for narrative and character analysis. This research uses a descriptive qualitative method by observing selected scenes, dialogues, and character interactions that show Ethan’s emotional, social, and psychological growth. The findings reveal that the film follows Field’s structure through the Setup, Confrontation, and Resolution, with each stage placing different pressures on Ethan that influence his decisions. Egri’s dimensions—physical, sociological, and psychological—also help illustrate how Ethan transforms from an anxious and overwhelmed officer into someone more confident, responsible, and emotionally grounded. Overall, this study concludes that combining narrative structure and character dimensions provides a clearer understanding of how the film builds tension and how the protagonist evolves throughout his journey.